Non-surgical management of superior mesenteric artery thrombosis using spinal cord stimulation. (5th August 2013) - Tod, Laura; Ghosh, Jonathan; Lieberman, Ilan; Baguneid, Mohamed
Abstract : We report the use of a spinal cord stimulator (SCS) for non-surgical management of superior mesenteric artery thrombosis. A 59-year-old woman with polycythaemia rubra vera presented with extensive superior mesenteric artery thrombosis not amenable to surgical or endovascular revascularisation. A SCS was implanted for analgesia thereby allowing enteral feeding to be tolerated during the acute period. Four months later the patient developed a focal ischaemic jejunal stricture and underwent resection of a short segment of small bowel with primary anastomosis that healed without complication. Spinal cord stimulation can facilitate non-surgical management of mesenteric ischaemia.